Hubungan Pola Makan, Aktivitas Fisik dan Pelayanan Kesehatan dengan Kejadian Diabetes Mellitus pada Lansia di Wilayah Puskesmas Pondok Gede Bekasi - Minda Patia Sari; Ahmad Farid Umar (Jurnal Persada Husada Indonesia, 2016)
Diabetes mellitus is a chronic disease due to impaired metabolism of carbohydrates, fats and proteins are characterized by elevated blood sugar levels. Some literature mentions the increasing prevalence of diabetes mellitus is usually influenced by the diet behavior and physical activity. The purpose of this study is to determine the relationship of health care, diet and physical activity with the prevalence of diabetes mellitus in the elderly in Puskesmas Pondok Gede Bekasi in 2013. The design of this research using the quantitative approach analytical method with case-control studies and supported qualitative methods depth interview. The sampling method is purposive sampling. Respondents were patients who visit the elderly Poly Health Center Pondok Gede Bekasi 60 respondents consisting of 30 respondents in the case group and 30 respondents in the control group. The informants were the patient's family who drove as many as three people and two health workers. The results showed a significant relationship between diet behavior and the prevalence of diabetes mellitus is r = -0.407 and a significant level of p = 0.002 and OR = 0.127. The relationship between physical activity with the prevalence of diabetes mellitus with r = -0.041 and p = 0.002 and OR = 0.182. Conclusion, there is a significant relationship between diet and physical activity and the incidence of diabetes mellitus in the elderly in Puskesmas Pondok Gede Bekasi. Qualitative studies show that elderly health care program at the health center and Posbindu still focused on medical examination and treatmen t. Preventive and Promotive activities such as gymnastics elderly and counseling not running optimally. Suggestions for improved dietary counseling program for people with diabetes and increase the frequency of elderly gymnastic activities to five times a week.